Analysis of Conceptual Understanding of Tenth-Grade Science Students on the Topic of Viruses Based on Learning Styles at MA Raudlatus Syabab Jember - Fatoni, Fajar; Nasution, Nanda Eska Anugrah; Iwan (Aspirasi Masyarakat Intelektual Islam Nusantara, 2025)
Conceptual understanding is a critical aspect of learning, particularly in biology, where students must grasp complex and abstract concepts. This study investigates the relationship between students' learning styles and their comprehension of the topic of viruses in a tenth-grade science class at MA Raudlatus Syabab Jember during the 2023/2024 academic year. A qualitative descriptive approach was employed, utilizing questionnaires, observations, and interviews to gather data from 34 students and their biology teacher. The findings indicate that visual learners exhibit strong comprehension when using images, diagrams, and structured notes; auditory learners perform better when engaging in discussions and listening to verbal explanations; and kinesthetic learners achieve deeper understanding through hands-on activities and practical demonstrations. However, each learning style presents unique challenges that can hinder comprehension if instructional methods are not aligned with students’ preferences. The study highlights the necessity of incorporating multimodal teaching strategies to cater to diverse learning styles, ensuring more effective knowledge retention and academic success.